2006
DOI: 10.1021/la061400o
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Behavior of a Perfluoropolyether Lotus-Leaf-like Topography

Abstract: We demonstrate the fabrication of 2-D arrays of nanopillars made from perfluoropolyether derivatives using a porous anodic aluminum oxide membrane as a template. Pretexturing the aluminum prior to anodization enables one to engineer multiple morphological length scales and thereby synthesize a lotus-leaf-like topography. Both nanopillars on a flat surface and on a lotus-leaf-like topology exhibit superhydrophobicity, low contact angle hysteresis, and self-cleaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
158
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(160 citation statements)
references
References 54 publications
1
158
1
Order By: Relevance
“…Others have focused on a toolbox of methods for creating these materials. A variety of superhydrophobic surfaces obtained using dry methods such as plasma modification, 26,40 laser etching, 41 and templating 42 and wet methods such as layer-by-layer deposition, 43 colloidal assembly, 44 electrospinning, [45][46][47] and solvent evaporation 48 have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have focused on a toolbox of methods for creating these materials. A variety of superhydrophobic surfaces obtained using dry methods such as plasma modification, 26,40 laser etching, 41 and templating 42 and wet methods such as layer-by-layer deposition, 43 colloidal assembly, 44 electrospinning, [45][46][47] and solvent evaporation 48 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of self-healing functionality to polymers provides a novel solution to this long-standing problem 36 (c) water strider leg nanogrooves, 36 and (d) lotus leaf. 13 (e-g) Synthetic superhydrophobic structures: (e) photolithographed posts, 33 (f) templated polymers nanofibers, 42 and (g) solvent structured surface. 48 and represents the first step in the development of materials systems with greatly extended lifetimes.…”
Section: Self-healing Polymersmentioning
confidence: 99%
“…To obtain polymer regular micro/ nano geometric surfaces, various nanoprocessing approaches can be employed, including nanoporous template wetting [15], capillary lithography [16], nanoimprint lithography [17], microstereolithography [18], template rolling press [19], and water spreading of carbon nanotubes [20]. A number of theoretical and experimental studies indicated that polymer aligned nanopillar arrays or carbon nanotube arrays could exhibit hydrophobic or surperhydrophobic feature [21][22][23][24]. As important as enhancing hydrophobicity of polymer surfaces, controlling hydrophilicity of polymer surfaces is also an interesting issue because most polymers are hydrophobic in nature that makes them unsuitable for important biomedical and industrial applications [25].…”
Section: Introductionmentioning
confidence: 99%
“…the water strider Notonecta glauca 9,10 . Fabrication of superhydrophobic materials usually require initial structuring with a hierarchical micro and nanopattern to increase surface roughness, 11,12 and a subsequent coating with low surface energy chemistry 13,14 . The surface coating does however represent at least one extra fabrication step and is best suited for coating of solid surfaces, such as that of Si with perfluorodecyltrichlorosilane (FDTS).…”
mentioning
confidence: 99%